Approaches in Teaching English based on 2013 Curriculum at SMPN 3 Poso Kota Utara - Ingriyani Y Rawung (Sintuwu Maroso Journal of English Teaching, 2018)
This research aims to describe the procedures of teaching English implemented by teachers of English at SMPN 3 Poso Kota Utara. This research is qualitative in nature. Data are collected by observation and documentation, then analyzed in two steps: firstly, the data of English learning process are observed then mapped to find a clearer description; secondly, procedure used during teaching and learning process are identified, and; thirdly, the procedures are decided in terms of appropriateness. The findings show that teachers of English at SMPN 3 Poso Kota Utara strictly followed lesson plan and syllabus as guidelines for teaching, used scientific learning as teaching approach, and the models of teaching and learning practice in this classroom are genre approach learning and discovery learning.Keywords: 2013 curriculum, teaching English, genre-based approach, discoverylearning approach